Integrasi Bitcoin dan Pasar Keuangan Global: Pendekatan ARDL Multi Aset - Sahrul Ramadhan; Ladi Wajuba Perdini Fisabilillah (Universitas Negeri Surabaya, 2026)
This study aims to analyze the level of Bitcoin integration with global financial markets, as represented by the S&P 500, Nikkei 225, Shanghai Composite, and gold indices. The research method uses the Autoregressive Distributed Lag (ARDL) approach to examine the long-term and short-term relationships between variables. The results show that Bitcoin has varying degrees of integration with global financial markets over the long term, while the relationship is more volatile in the short term. These findings suggest that Bitcoin has not yet fully functioned as a stable safe haven, but still has potential as an investment diversification instrument. In conclusion, Bitcoin's movements are still influenced by global market dynamics, so investors need to consider the risk of volatility in making investment decisions.